If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = 8 + -1x * 7 Reorder the terms for easier multiplication: -10 = 8 + -1 * 7x Multiply -1 * 7 -10 = 8 + -7x Solving -10 = 8 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -10 + 7x = 8 + -7x + 7x Combine like terms: -7x + 7x = 0 -10 + 7x = 8 + 0 -10 + 7x = 8 Add '10' to each side of the equation. -10 + 10 + 7x = 8 + 10 Combine like terms: -10 + 10 = 0 0 + 7x = 8 + 10 7x = 8 + 10 Combine like terms: 8 + 10 = 18 7x = 18 Divide each side by '7'. x = 2.571428571 Simplifying x = 2.571428571
| -21=7u+7(u-7) | | 3(6z+7)+10z+45=180 | | 4x^2-7x-57=0 | | (2x-30)=45 | | (x^2-1)=0 | | w-16=-3 | | x+(x+4)=50 | | 4x-19=13x-1 | | 2(x-6)=7 | | 3(6z+7)10z+45=180 | | 2/3(3x+1)=5 | | -1.25+0.5x=0 | | 9x-7=12x-4 | | 3x*3y= | | 20+8(a-11)=-12 | | 9x-7=12-4 | | x^2+8xy+16y^2-4x-16y+7=0 | | -3(2x+3)=-6x+9 | | f(-1.5)=3x^2-6x+3 | | x-11(13+4x)=-3(5-9x)+2 | | 3x+2=9x+6 | | (x-3).4=8 | | 8(3x-2y)+4[(-3x)+4y]= | | 5x-4=8x+5 | | 2.35(4x-4)=-2+10x+12 | | x+23=69 | | 5n-3[n-5]=13 | | 11x+3=9x-11 | | Y-13=-45 | | 4-x=4(x+2) | | (3p-6)+90= | | abs(15x-7)=5abs(x+3) |